(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper presents universal data management through web base configurable system. Universal data stands for most of analog signal which are useful for mankind and industrial system. 24bit ADC provides high resolution data. We have tried data acquisition for multiple applications. Data frequency and channels can be customized through web base configurable system. Data can be logged with set frequency with real time stamp and this data is available on web. Remote access of the data, makes the system very useful and low cost solution. data can be collected from remote locations. HTML/.NET script is used to develops web pages and their GUI application. Embedded hardware contains Ethernet [10/100 base-T, RJ45 connector] base microprocessor RCM3700 having 512KB memory for storing the web pages. By using a low cost network communication module (RCM 3700) as a web server, one can achieve better network security, lower power consumption, compact size, and easier to use at remote places. Results show the remote monitoring and control system [RMACS] with data log. Low cost web server for collecting high resolution data with multiple channels provides best solution for many applications